Visible‐Light‐Photosensitized Aryl and Alkyl Decarboxylative Functionalization Reactions. Issue 31 (3rd July 2019) - Patra, Tuhin; Mukherjee, Satobhisha; Ma, Jiajia; Strieth‐Kalthoff, Felix; Glorius, Frank
Abstract: Despite significant progress in aliphatic decarboxylation, an efficient and general protocol for radical aromatic decarboxylation has lagged far behind. Herein, we describe a general strategy for rapid access to both aryl and alkyl radicals by photosensitized decarboxylation of the corresponding carboxylic acids esters followed by their successive use in divergent carbon–heteroatom and carbon–carbon bond‐forming reactions. Identification of a suitable activator for carboxylic acids is the key to bypass a competing single‐electron‐transfer mechanism and "switch on" an energy‐transfer‐mediated homolysis of unsymmetrical σ‐bonds for a concerted fragmentation/decarboxylation process. Abstract : Divide et impera : A general strategy to access both aryl and alkyl radicals by photosensitized decarboxylation of the corresponding carboxylic esters is based on an energy‐transfer‐mediated homolysis of unsymmetric σ‐bonds. The independent aryl/alkyl radical generation step enables a series of key C−X and C−C bond‐forming reactions by simply changing the radical trapping agent.